A influência do Instagram no consumo online dos discentes em uma IES - Siqueira, Antônia Andreza da Silva (Universidade Federal Rural do Semi-Árido, 2019)
Consumption is part of the routine of the human being and with the evolution of ecommerce there are tools that facilitate the life of consumers and potentialize their practices. The present study has as general objective to analyze the influence, use and applicability of the social network Instagram in the online consumption of the students of a Higher Education Institution (IES). Quantitative descriptive analysis was used as methodology. We used a questionnaire already prepared by the author Silva (2017) for data collection, where the online questionnaire was launched on social networks facebook, whatsapp and also a data collection with printed questionnaires distributed to the students of the Federal Rural University of Semi- Árido (UFERSA), Angicos campus, obtaining a sample of 150 respondents. The collected data were treated in the SPSS software, using the descriptive and inferential statistics modules, factor analysis, analysis of variance (ANOVA). From the data analysis, it was concluded that the Instagram social network has little influence on the analyzed sample and that the greatest influence of online shopping comes from the primary reference given by relatives such as parents and sibling (s). The factors influencing the online purchase intention of the students who are social influencers, information search, perception and learning, frequency of use and primary reference were also obtained.
Monografia
Keywords: Internet; Instagram; Consumo; Influência e IES; Internet; Instagram; Consumption; Influence and IES; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::SISTEMAS DE INFORMACAO